Development Of Project Based Learning-Based Video Tutorials in Vocation High School - Fahrul Rozi; Humisar Sihombing; Abdul Hamid K; Keysar Panjaitan; Kornelius Harefa (International Journal of Economic, Technology and Social Sciences (Injects), 2022)
This research aims to: (1) know the feasibility of the media Video tutorial based on the project based learning software application and interior building, and (2) to determine the effectiveness of the use of media video tutorial based project based learning on software application learning and building interiors can improve the learning outcomes of software applications and building interiors. This type of research is development research using R&D models from the Borg and Gall combined with the Dick and Carey instructional design models. The method used in this study is a quasi-experimental method. The results of the hypothesis test study prove that there is a significant difference between the learning outcomes of software applications and building interiors that are studied using project-based learning video tutorial media and the learning outcomes of software applications and building interiors using visual media.